Behavioral and monoamine changes following severe vitamin C deficiency. (30th November 2012) - Ward, Margaret S.; Lamb, Jonathan; May, James M.; Harrison, Fiona E.
Abstract Severe vitamin C deficiency (ascorbic acid; AA) was induced in gulo−/− mice incapable of synthesizing their own AA. A number of behavioral measures were studied before and during the deprivation period, including a scorbutic period, during which weight loss was observed in the mice. Mice were then resuscitated with AA supplements. During the scorbutic period, gulo−/− mice showed decreased voluntary locomotor activity, diminished physical strength, and increased preference for a highly palatable sucrose reward. These behaviors all returned to control levels following resuscitation. Altered trial times in subordinate mice in the tube test for social dominance in the AA‐deprived mice persisted following resuscitation and may signify a depressive‐like behavior in these mice. Biochemical analyses were undertaken following a second deprivation period. AA deficiency was accompanied by decreased blood glucose levels, oxidative damage to lipids and proteins in the cortex, and decreases in dopamine and serotonin metabolites in both the cortex and striatum. Given the reasonably high proportions of the population that do not consume sufficient AA in the diet, these data have important implications for physical and psychological function in the general population.